Effect of bortezomib in combination with cisplatin and 5-fluorouracil on 4T1 breast cancer cells - Yerlikaya, Azmi; Altıkat, Sayit; Irmak, Reyhan; Cavga, Fatma Zehra; Kocacan, Sultan Aysun; Boyacı, İhsan (Spandidos Publications, 2013)
Bortezomib is a highly selective and reversible inhibitor of the 26S proteasome. It has been approved for the treatment of patients with relapsed and refractory multiple myeloma. A number of studies have been conducted to evaluate. the activity and safety of bortezomib either alone or in combination with several cytotoxic agents and radiation. In the current study, the efficacy of bortezomib alone or in combination with cisplatin and 5-fluorouracil was evaluated in 4T1 breast cancer cells, a highly metastatic murine cancer cell line. Using MTT assay, IC50 values of cisplatin and 5-fluorouracil were determined to be 14.2 and 8.9 mu M for cisplatin and 5-fluorouracil, respectively. The effects of different concentrations of cisplatin and 5-fluorouracil in combination with two different concentrations of bortezomib were examined in the 4T1 cells. Statistically significant differences were found when 1 or 5 mu M cisplatin was combined with 10 or 50 nM bortezomib. Similarly, 1 mu M 5-fluorouracil or 5 mu M 5-fluorouracil in combination with 10 nM bortezomib caused significant cell death as compared to treatment with single agents. However, 1 or 5 mu M 5-fluorouracil did not potentiate the effects of higher concentrations of bortezomib (50 nM). The effect of the combination of cisplatin, 5-fluorouracil and bortezomib was determined by soft agar assay. It was confirmed that a combination of cisplatin and bortezomib was more effective than each drug as a monotherapy. Therefore, the combination of cisplatin and bortezomib should be tested further in clinical settings.
WOS: 000321079300046
PubMed ID: 23660746
Keywords: Bortezomib; Cancer; Cisplatin; 5-Fluorouracil